STREET CHILDREN: A QUEST FOR BASIC HUMAN RIGHTS - Agrawal, Nitish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The notion that children are assets and the hope of a nation reflects a widely held perspective emphasizing the importance of investing in and nurturing the well-being and development of the younger generation. Socioeconomic rights play key roles in the life of homeless kids and street children because kids are at additional risk as compared to grown up children and for a long time they have been subjected to hatred and discrimination. Therefore, street children need exceptional safeguard of their basic fundamental rights by acquiring of positive and uniform secure measures. The issue is a complex one with various factors contributing to their condition. In this research, we examine the challenges the street children face and understand the root causes behind their situation. We also try to draw attention towards socio economic elements contributing to homeless children living a street life or societal and cultural perspectives towards street children. Our study will also focus on case studies highlighting effective programs, community-based approaches, emphasizing the importance of a global perspective in addressing street children issues. Lastly, this research will accord with additional steps and measures that can be taken to overcome street children’s hurdles and address the struggles faced by street children.